2022
DOI: 10.1177/19417381221116319
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Outcomes in Early Postoperative Management After Shoulder Surgery Using a Home-Based Strengthening and Stabilization System With Telehealth

Abstract: Background: Multiple rehabilitation protocols after shoulder surgery have been proposed. The coronavirus pandemic adds an extra layer of complexity to postoperative rehabilitation after shoulder surgery. Hypothesis: The combined use of a home-based rehabilitation system, the Shoulder Strengthening and Stabilization System (SSS), and telehealth visits will lead to acceptable patient self-reported outcomes and satisfaction after shoulder surgery. Study Design: Prospective observational cohort. Level of Evidence:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…The DR group participants reported high satisfaction levels with the use of the digital healthcare system in terms of real-time feedback, programs supported by experts, and rehabilitation service without transportation concerns. These ndings are in line with those of a previous study that showed a high satisfaction level with a home-based strengthening and stabilization system after shoulder surgery 30 .…”
Section: Discussionsupporting
confidence: 92%
“…The DR group participants reported high satisfaction levels with the use of the digital healthcare system in terms of real-time feedback, programs supported by experts, and rehabilitation service without transportation concerns. These ndings are in line with those of a previous study that showed a high satisfaction level with a home-based strengthening and stabilization system after shoulder surgery 30 .…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have also studied aggressive versus increased immobilization protocols and have not demonstrated an advantage to one over the other. [14][15][16][17][18] Rehabilitation programs may be individualized to the patient depending on age, size of tear, and activity level of the patient. It takes 12 weeks for a rotator cuff tendon to heal completely to bone and develop Sharpey's fibers.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…19 Complete rehabilitation and return to full activity often takes 4 to 6 months and may take up to 1 year. [14][15][16][17][18] Results vary and are correlated with the size of the tear and the age of the patient.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine primäre physisch präsente Unterweisung des Patienten in sein physiotherapeutisches Nachsorgeschema in der erstbehandelnden Institution erscheint als Ausgangspunkt zur Einleitung der postoperativen Nachbehandlung nach einem Gelenkersatz sinnvoll [ 6 ]. Die Kombination aus analoger und digitaler Nachsorge scheint als ideale Ausgangsposition ein Zukunftspotenzial zu offerieren.…”
Section: Orthopädie Und Unfallchirurgie Und Die Telerehabilitationunclassified